The Relationship Between University Climate And Inertia According To Preservice Teachers' View - Cankaya, Ibrahim H.; Demirtas, Zulfu (Pamukkale Univ, 2010)
The aim of this study to research the reletionship between university climate and inertia according to preservice teachers' perception. The research is in survey model. The questionnair were dealed to all the preservice teachers in Firat University Faculty of Education downtown in 2008-2009 academic year. Data obtained from 277 questionnaires that were returned back were analyzed. University climate scale was development by Johnson, Johnson, Douglas ve Zimmerman (1999), inertia scale was development by Liao, Fei ve Liu, (2008). The end of the research it has been realized that the university climate have routed meaningly the inertia of the preservice teachers. It has been realized that there is a reverse relationship between the inertia and university climate. It has been seen that it needs to focus on the motivation and social activities of the preservice teachers in universities.
Keywords: Inertia; Motivation; Organization Climate; Social Opportunities